(E-)Learning to Understand and Love Yourself: An Attempt to Teach Healthy Lifestyle in the Midst of Social Unrest - Lee Wai Sum, Amy (Frontiers in Education, 2021)
A major curriculum reform in 2012 changed the Higher Education curriculum in Hong Kong as one more year was added to most degree programmes, allowing good opportunities to provide General Education to students in all major disciplines. The compulsory General Education programme is an important component in the nurturing of young adults to become responsible members of society, as well as providing them with necessary knowledge and skills for lifelong learning. The structure, units allocation, and actual course content of these GE courses in local universities differ, what they share is a comprehensive coverage across knowledge areas: the arts, the social and natural sciences, and skill sets that students can apply in personal and professional life. The author of this article comes from a Hong Kong university that offers a General Education programme with courses designed and taught by individual academic departments and supported by relevant administrative units. This article is a sharing of and reflection on the experience of teaching a General Education course in the category of Healthy Lifestyle, open to full-time students of all disciplines, during the fall semester of academic year 2019-2020. During most of the semester, daily life in Hong Kong had been disrupted to different extents, and the emotional landscape across different population groups had been rugged. University students were also affected physically and emotionally during this time, the teaching and learning environment was challenged, and teachers had to create an appropriate teaching and learning experience in view of the external environment and the students’ internal emotional needs. This article shares some useful practices in employing e-learning during a time of unrest, to facilitate the teaching of healthy lifestyle to students. The learning outcomes achieved, as seen in some student work, encourage us to reflect on how further we can employ e-learning to create more effective learning experience for new generations of students, especially in the area of affective learning.